984 Population-Based Study to Evaluate the Neonatal Morbidity and Mortality in Maternal Diabetes. (October 2012) - Lange, A; Spoo, R; Thyrian, R; Hoffmann, W; Lode, H; Heckmann, M
Abstract : Aim: The aim of the study is to determine any connections between maternal diabetes and the pregnancy outcome of mothers and newborns. Methods: From 03/2003 to 11/2008 in local and university hospitals in Northeast Pomerania, Germany a total of n=4593 mothers and their children were used as a prospective population-based birth cohort. The objective of the survey of newborns in Pomerania (SNiP) is to evaluate the negative pregnancy outcome, morbidity and mortality in diabetes affected pregnant woman. A comparison of glucose-intolerance affected childbearing mothers (n=243) identified by oral glucose tolerance test and non-diabetic mothers (n=4350) were conducted. Results: The prevalence of maternal glucose-intolerance is 5.3%. Comorbidity of maternal diabetes is more prevelant with higher age, greater number of previous pregnancies (parity) and those who are overweight (relative risk 1.97). Macrosomi (OR=2.28) and reduced gestational age are identified as a fetal risk factors. As a maternal risk factor is considered positive vaginal infection (OR=1.97). As a negative outcome a higher rate of Cesarean section, instrumental delivery (OR=1.96) and pathologic final delivery positions (15.3% non-diabetes/9.3% diabetes) can be observed. This all leads to a four times higher odds ratio of post-partus hospitalization (OR=3.70) and mandatory pre-partus therapy (OR=4.78) of the diabetes affected group. Conclusions: Newborns of mothers with gestational diabetes demonstrate a fetopathia diabetica with makrosomi and immaturity which leads to higher rate of birth complications and post-partus hospitalisation of almost every second newborn. An increased risk for mothers and their children exists in case of gestational diabetes.